Two Half Lives - Golbol, Servet Ahmet (Germany : IMPALA Filmproduktion, 2008)
Reincarnation is the subject of “Two Half Lives.” The filmmaker portrays children who say that they have lived before. Not sometime or somewhere but just before this life, in the same place – Antakya, south of Turkey. Their families are convinced of the truth of their stories because of the numerous facts presented by the children however, the children themselves are not happy. They are conflicted between two identities. As a son of Turkish migrant workers who moved to Germany in the 1970s, the filmmaker also poses questions about his own history. He, too, has to combine two different lives, two cultures. Seeking advice, he turns to the town’s religious leaders. He talks with the patriarch of the Orthodox Church, the imam of the Habib Neccar Mosque, the Jewish community council, and one of the most respected Alevi sheikhs. The stories of the four children unfold and intertwine with the filmmaker’s experience, the link being Antakya.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films